KAJIAN YURIDIS UANG WAJIB TAHUNAN OTORITA ATAS PEMBERIAN HAK MILIK DIATAS HAK PENGELOLAAN DI KOTA BATAM - MEGA H. ANDIKA (PREMISE LAW JURNAL, 2016)
The Agrarian law which is effective in Indonesia is based on tenure which can be proved by various tenures on land. The state’s tenure is the State’s authority to organize or to distribute authorities on land. HPL (the right to manage) which is part of the state tenure is owned by BP Kawasan and as an administrator BP Kawasan exempts Authoritative Yearly Required Money to the holder of land rights, including ownership. Actually ownership as the most powerfull and unlimited right is not required to pay UWTO, but HPL and its land management do not break up end so that they become the factor of the bound between the holder of the land rights and BP Kawasan. The land problem in Batam is only related to the overlapping land regulation but also to two authorities. BP Kawasan as the holder of HPL has the obligation to register the HPL and the authority to give and distribute parts of HPL land which is requested to become land rights throught an agreement as the basis for the applicant for the rights in registering the new land rights in order to get legal certainly. The entire land in Batam is generally controlled by BP Kawasan, but there are some parts of it which are not registered; they are known as ”kampung tua”(old village). Ideally the land rights given from HPL are affordable, but some of distributed land has been changed to ownership by increasing its right status. Keywords: Right to Manage, Ownership, Authoritative Yearly Required Money